Metaphor and the Mind of God in Nevi'im - Nordby, S. N. (TheoLogica, 2018)
In The Philosophy of Hebrew Scripture, Yoram Hazony contrasts the uses of metaphor in Nevi'im and the New Testament. According to Hazony, metaphor is employed by Jesus to obscure teachings, but the prophets of the Hebrew Scriptures use metaphor to make teachings intelligible. However, this understanding of metaphor is too simplistic to capture the scope of metaphorical statements made by the Hebrew prophets. In this paper, I suggest that an important set of philosophical arguments are advanced by the prophets in ways not captured by current interpretive methodologies. The paper is divided into two parts. In the first half, I argue against Hazony's assessment of Nevi'im. In the second, I forward my position on the philosophical dimensions of Nevi'im: that prophetic writings reveal important moral facts about God's nature and the ways in which we should respond to him in both action and emotion. Appealing to the works of Dru Johnson, Eleonore Stump and Linda Zagzebski, I show that the writings of the Hebrew prophets may in fact advance certain arguments about the emotions and motivations of God. Through the collected writings of Nevi'im, God functions as an exemplar for those receiving the words of the prophets.